Comment peut-on faire du people ? - Jamil Dakhlia (Communication)
Through interviews with managers and senior executives of some of France’s celebrity weeklies, we first examine the structural constraints dictated to the editorial staff by both photo agencies and celebrities. Then we explore the “subjective sphere” and the “economies of worth” of gossip columnists, showing how they negotiate with their derogatory public image in order to give meaning to their professional role.